THE USE OF TRANSLATION TOOL IN ARGUMENTATIVE WRITING PROCESS - Fadhillah, Elsya Ayu; Irawati, Tatik (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2024)
The purpose of this research to find out how English students use translation tools in the process of argumentative writing. This research was conducted qualitative method by using audio-visual materials in the form of screen recordings of students' writing and questionnaires in the form of a combination of closed and open-ended questionnaires. The results showed the planning stage, students used Google Translate to check the meaning of unknown words, translate phrases, translate clauses and translate sentences. Then, students use DeepL Translator to check the meaning of unknown words, translate phrases and translate sentences, also use Microsoft Word Translator to check the meaning of unknown words, translate phrases, translate clauses and translate sentences. At the drafting stage, students use Google Translate to translate clauses, sentences and paragraphs. In addition, students use DeepL Translator to translate sentences and paragraphs. At the editing stage, students use Google Translate to check the meaning of unknown words and translate clauses. Finally, at the final draft stage, students have finished writing, so they no longer use translators at this stage.